Public relations writing - Mahoney, James Scott, 1947- (South Melbourne, Vic. : Oxford University Press, 2013)
'Public Relations Writing 2e, approaches public relations as an ethical and professional element of strategic organisational management. It encourages students to regard themselves as beginning practitioners who need to understand the social, economic, political and multicultural contexts in which they work. The book deals with writing from a professional practice perspective but refers where appropriate to relevant communication theories. It includes tools to help plan, write and implement public relations strategies and tactics.' -- Publisher website.
Public relations toolkit -- Introduction -- Tip sheet : the importance of language -- Contexts for public relations -- Research and planing for public relations -- Tip sheet : multicultural communication -- Public relations goals and objetives -- Developing and writing messages -- Writing and placing a media release -- Tip sheet : writing a media release -- Writing for social media and the web -- Tip sheet : social media writing tips -- Interpersonal communication -- Beyond the mass news media -- Communicaiton within organisations -- Getting the job done -- Writing a public relations evaluation plan -- A reflection -- Glossary -- References -- Index.
Originally published : Public relations writing in Australia. 2008.
Includes bibliographical references : pages 211-215 and index.
Keywords: Public relations -- Australia; Written communication -- Australia; Business communication -- Australia